Creativity of Protection of Rape Victims in Victimological Perspective - Al Faraby, Muhammad Faisal (Journal of Creativity Student, 2019)
Society tends to think that it is women who have a weak figure. So there is a patriarchal culture that makes women often become victims of rape crimes committed by irresponsible men. The many types related to sexual violence given to female victims are realized in the form of rape that occurs. There are many bad effects caused by explaining the crime of non-urban crimes committed by the perpetrator against the victim, giving a real impact on the mental and giving suffering to the victim, it is also part of the violation of human rights against women. Research conducted by researchers with the aim of knowing the reasons for the importance of getting protection and security for rape victims. So that in the process of carrying out the research, normative legal research is used, and assisted by the use of secondary data which is considered and used as the most important data in research, and primary data which is only as a support. The result of this research is that the crime of rape committed by the perpetrator will have a multiplier impact on the victim so that protection and security for the victim is needed for the crime.